2016
DOI: 10.1063/1.4966041
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of interface states by hydrogen treatment at the aluminum oxide/4H-SiC Si-face interface

Abstract: Processes to form aluminum oxide as a gate insulator on the 4H-SiC Si-face are investigated to eliminate the interface state density (DIT) and improve the mobility. Processes that do not involve the insertion or formation of SiO2 at the interface are preferential to eliminate traps that may be present in SiO2. Aluminum oxide was formed by atomic layer deposition with hydrogen plasma pretreatment followed by annealing in forming gas. Hydrogen treatment was effective to reduce DIT at the interface of aluminum ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Peak field effect mobility of 106 cm 2 V −1 s −1 using a gate dielectric of thin nitrided SiO 2 and Al 2 O 3 was reported by Lichtenwalner et al [13]. Hydrogen plasma treatment was found to be effective at decreasing the interface state density at the Al 2 O 3 -SiC interface [14,15], resulting in a peak field effect of mobility of 57 cm 2 V −1 s −1 with a density of interface traps of 1.7 × 10 12 at E C − E = 0.2 eV using the C-ψ technique.…”
Section: Introductionmentioning
confidence: 75%
“…Peak field effect mobility of 106 cm 2 V −1 s −1 using a gate dielectric of thin nitrided SiO 2 and Al 2 O 3 was reported by Lichtenwalner et al [13]. Hydrogen plasma treatment was found to be effective at decreasing the interface state density at the Al 2 O 3 -SiC interface [14,15], resulting in a peak field effect of mobility of 57 cm 2 V −1 s −1 with a density of interface traps of 1.7 × 10 12 at E C − E = 0.2 eV using the C-ψ technique.…”
Section: Introductionmentioning
confidence: 75%
“…A variety of SiC surface-cleaning treatments have been proposed, based either on wet chemical solutions [44][45][46] or plasma [47][48][49]. The most used chemical solutions for SiC cleaning are combinations of diluted sulfuric acid, hydrogen peroxide, isopropanol, diluted hydrofluoric acid.…”
Section: Growth Of Amorphous High-κ Oxides On Sicmentioning
confidence: 99%
“…Suvanam et al [46] demonstrated that RCA treatment [45], followed by HF diluted solution and finally isopropanol, was a good route to improve the interfacial electrical characteristics of Al 2 O 3 films on SiC, obtaining a density of interface states D it = 1.5 × 10 11 eV −1 cm −2 at E C − E t = 0.2 eV below the 4H-SiC conduction band edge, which was about two orders of magnitude lower than the values found with thermal SiO 2 . In regard to plasma treatment before high-κ deposition, H 2 plasma has been also evaluated in some works [47][48][49], since it represents an efficient route for the passivation of dangling bonds on SiC surfaces. Heo et al [49] measured promising values of interface state density (D it = 6 × 10 12 eV −1 cm −2 at E C − E t = 0.2 eV) when a 15 min long H 2 plasma treatment was performed before deposition and after the post-metallization step.…”
Section: Growth Of Amorphous High-κ Oxides On Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…The D it of the ALD-Al 2 O 3 /4H-SiC interface was lower than that of the SiO 2 /4H-SiC interface without a post-annealing process at high temperatures. 21,22) The third was Al 2 O 3 formed via metal layer oxidation (MLO). We proposed MLO in a previous work.…”
Section: Introductionmentioning
confidence: 99%